Expanding the phenotype in Pitt-Hopkins syndrome; description of new oral finding and dental management considerations - Yazan Hassona; Dua'a Alqaisi; Asma Alkilani; Iyas AbuHijleh (BMC, 2024)
Abstract Background Pitt-Hopkins syndrome (PTHS) is a rare neurodevelopmental disorder with physical, cognitive, and behavioral characteristics that is caused by heterozygous mutations in the TCF4 gene. Patients with PTHS might present a unique challenge for oral healthcare professionals because of the associated comorbidities. Case report Here we describe a new case of PTHS in a 13-year-old girl with particular emphasis on oro-dental findings and oral healthcare management. Observed oro-dental findings in our case included shallow palate, absence of lingual frenum, gingival enlargement, thick lips and relative microdontia. The patient was unable to tolerate dental care under local anesthesia. Therefore, comprehensive dental treatment was performed under general anesthesia after a careful pre-anesthetic cardio-respiratory, neurological, and hematological evaluation. The patient was closely monitored intra-operatively for breathing rhythm, O2 saturation, and signs of respiratory distress. The patient was observed for 24 h post-op for respiratory distress and was discharged then uneventfully. Conclusion Dental treatment under general anesthesia in these patients might be complicated by the abnormal breathing rhythm, and close monitoring and follow up for signs of respiratory distress after general anesthesia is necessary. Recognition of oral and dental findings might help to expand the phenotype and better characterize rare syndromes.